A molecular update on the origin of the carpel. (February 2020) - Becker, Annette
Abstract : Carpels, the female reproductive organs of flowering plants, are of major economic importance since much of our food is ultimately derived from carpel tissue and they are a defining innovation for flowering plants. Amazingly, little is known about the origin and conservation of the developmental program of the carpel besides the knowledge generated by utilizing Arabidopsis thaliana . However, in the past few years advances in ancestral state reconstruction, developmental genetics, and phylogenetic analyses led to advances in the field of flower evodevo. Here, I summarize recent work on ancestral state reconstructions of carpels, and the functions of the major components of the genetic networks governing carpel development described for Arabidopsis. Then, I point out how the stepwise addition of genes during land plant evolution has generated the A. thaliana carpel's developmental toolkit. By merging these observations, I propose a basic version of the ancestral angiosperm carpel developmental network.